2005
DOI: 10.1086/430388
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Optimal Structure Required for a Shiga Toxin Neutralizer with Oriented Carbohydrates to Function in the Circulation

Abstract: Shiga toxin (Stx) is a major virulence factor of Stx-producing Escherichia coli. Recently, we developed a therapeutic Stx neutralizer with 6 trisaccharides of globotriaosyl ceramide, a receptor for Stx, in its dendrimer structure (referred to as "SUPER TWIG [1]6") to function in the circulation. Here, we determined the optimal structure of SUPER TWIG for it to function in the circulation and identified a SUPER TWIG with 18 trisaccharides, SUPER TWIG (2)18, as another potent Stx neutralizer. SUPER TWIGs (1)6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 22 publications
3
116
0
1
Order By: Relevance
“…To date, many successful examples of antivirulence therapeutic studies have focused on abrogating the effectiveness of toxins, be it through direct inhibition of activity, delivery, or attachment to the host cell (18)(19)(20). One such study utilized a glycomimetic approach to inhibit Shiga toxin's recognition of the host receptor, globotriaosylceramide, which has proven to be effective in vitro and in animal models of enterohemorrhagic Escherichia coli infections (21,22). Similarly, the monoclonal antibody raxibacumab targets the protective antigen component of anthrax toxin (23) and was approved by the FDA in 2012 for protection against and treatment of inhaled anthrax (23)(24)(25).…”
Section: Antivirulence Therapiesmentioning
confidence: 99%
“…To date, many successful examples of antivirulence therapeutic studies have focused on abrogating the effectiveness of toxins, be it through direct inhibition of activity, delivery, or attachment to the host cell (18)(19)(20). One such study utilized a glycomimetic approach to inhibit Shiga toxin's recognition of the host receptor, globotriaosylceramide, which has proven to be effective in vitro and in animal models of enterohemorrhagic Escherichia coli infections (21,22). Similarly, the monoclonal antibody raxibacumab targets the protective antigen component of anthrax toxin (23) and was approved by the FDA in 2012 for protection against and treatment of inhaled anthrax (23)(24)(25).…”
Section: Antivirulence Therapiesmentioning
confidence: 99%
“…Earlier studies had shown that simple oligosaccharides mimicking the receptor structure were not particularly potent toxin inhibitors. However, vastly improved toxin binding kinetics were achieved when analogous oligo saccharides were displayed on complex molecular scaffolds that optimized multivalent docking with the B pentamer [2][3][4][5]. At least in some cases, protection in animal [4,5].…”
Section: Toxin-receptor Blockade As An Anti-infective Strategymentioning
confidence: 99%
“…However, vastly improved toxin binding kinetics were achieved when analogous oligo saccharides were displayed on complex molecular scaffolds that optimized multivalent docking with the B pentamer [2][3][4][5]. At least in some cases, protection in animal [4,5]. However, notwithstanding the elegance of the underlying chemistry, such multivalent synthetic ligands are likely to be expensive to produce on a large scale.…”
Section: Toxin-receptor Blockade As An Anti-infective Strategymentioning
confidence: 99%
“…Finally, we determined the binding sites of various Gb3 polymers on the Stx1 and Stx2 B subunits by using a series of 1BH and 2BH with mutations at the trisaccharide-binding sites (15). Kinetic analysis was performed by using the BIAcore system.…”
Section: Shiga Toxin (Stx) Is a Major Virulence Factor In Infections mentioning
confidence: 99%